STUDI KORELASIONAL ANTARA POWER LENGAN, FLEKSIBILITAS, DAN MOTIVASI BERPRESTASI DENGAN HASIL PUKULAN FOREHAND GROUNDSTROKE - Agusni, Dhani (Jurnal Olahraga, 2015)
This research is to find the relationship and influence of arm strength, flexibility, achievement motivation on the results of field tennis forehands. The method used in this study uses a survey method using korelasoinal. The number of samples used was 11 students who are members and active in UKM tennis field. Data collection tools used consisted of a questionnaire, namely a questionnaire about achievement motivation and tests for arm power tests, were discussed, and forehand tests consisted of speed and accuracy. The results obtained are arm strength that is collected and has a positive relationship with the results of the forehand, denies and has a positive relationship with the results of the forehand, as well as related achievement motivation and has a positive relationship with the results of the forehand. The next research results are all three and have a positive relationship with the results of the forehand.